FOOD EMULSIFIERS IN BREAD PRODUCTS AND IMPROVING THE NUTRITIONAL QUALITY OF BREAD PRODUCTS - Rahimova Aziza Rashidovna (Web of Journals Publishing, 2024)
This article presents ideas on the proper use of food emulsifiers and increasing the nutritional value of bread products due to the development of the food industry.
Keywords: emulsifier, fermentation, gluten, starch, trace elements, wheat flour.